IDENTIFIKASI BERBAGAI ALASAN PENYEBAB SUAMI BERPOLIGAMI - Soediro Soediro (Kosmik Hukum, 2012)
Polygamy is not a new law which is the product of Islam as it existed before the arrival of Islam. In times of ignorance even Shoqoliyah community, that society as we know now the Russian state, Yugoslavia, and about this Bolonia have practiced polygamy. Islam came and gave the terms and limitations more clearly in the practice of polygamy.Understanding the terminology referring to polygamy is God's instructions that allow polygamy to four wives provided that fair to them. If you can not do justice, then just one wife (monogamy). This research is a descriptive normative studies using qualitative case study method, which is intended to provide a clear and comprehensive overview of the permission for polygamy by the examination in a court case, with reference to existing norms. Determination of the location of the research undertaken purposively in Navan Religious Courts jurisdiction. Things that underline the petition is granted permission for polygamy is that wife is not able to serve the needs of the most biologically husbands, wives do not have offspring (sterile), the husband of a relationship with another woman and feared happened adultery, the husband has impregnated another woman, the wife rarely gave the inner income to the husband. Key words: Polygamy, Religious Courts.